What is Sphenomorphus maculatus (Blyth, 1854 “1853”) (Reptilia: Squamata: Scincidae)? Validating cryptic diversity and the designation of a neotype - Borah, Pranoy Kishore; Grismer, L. Lee; Das, Abhijit; Purkayastha, Jayaditya; Deuti, Kaushik; Lalremsanga, Hmar Tlawmte; Datta-Roy, Aniruddha (Zootaxa, 2024)
The Spotted Litter Skink, Sphenomorphus maculatus, initially described by Edward Blyth in 1854, lacks a taxonomic reference point, as the holotype was reported lost by 1868. A preliminary molecular phylogenetic analysis revealed indications of cryptic diversity within S. maculatus across its range in Northeast India. We aimed to pinpoint the precise type locality, concluding that it corresponds to the peripheral forested regions surrounding Guwahati, India. To establish a robust taxonomic foundation for future investigations, we designate a neotype under the provisions of the ICZN Code (Article 75). We also provide a comprehensive redescription of the neotype. This analysis and redescription were based on recently collected specimens from the identified type locality, and approximate areas based on the movements of Col. Jenkins, who was the original collector of the holotype. Genetic data from six loci of the neotype and from the other specimens were deposited in GenBank, contributing valuable information for future reference.